Anno's Italy - Anno, Mitsumasa, 1926; Kobayashi, Miki, 1968- (San Luis Obispo, CA : Beautiful Feet Books, 2018)
Scenes of Italian daily life of the past and present are interwoven with the theme of the life of Christ as depicted in famous Italian religious paintings.
"Originally published by Fukuinkan Shoten Publishers, Inc., Tokyo, Japan, in 1978 under the title of "Tabi no ehon II"--Title page verso.
Keywords: Stories without words; Italy -- Pictorial works